Peningkatan Keterampilan Menyajikan Data Dalam Bentuk Tabel dan Diagram Batang Melalui Model Pembelajaran Kooperatif Tipe STAD - Januantika, Anggie Tri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve mathematics learning outcomes for grade IV students of SD Negeri 1 Demangan for the 2018/2019 academic year through STAD type cooperative learning. This research is a Classroom Action Research which was carried out in two cycles of improvement. Each cycle includes 4 stages, namely: planning, implementing actions, observing and reflecting. The success indicator of this research is if more than 85% of the fourth grade students of Elementary School 1 Demangan, Karangdowo, Klaten get a score of >65 or complete the KKM. In the study, it was found that student learning outcomes in the pre-cycle were the average value of 59,25 and the percentage of completeness was 41,67%, the first cycle was the average value of 67,25 and the percentage of completeness was 75%, while in the second cycle the average value was obtained. the average is 75,9 and the percentage of completeness is 91,67%.